Studies on immune impairment in chronic Hepatitis C virus infection / Barathan Muttiah - Barathan, Muttiah (2016)
Hepatitis C virus (HCV) is a blood-borne pathogen that infects hepatocytes and causes widespread destruction to the host immune system. Estimates suggest that HCV has infected ~200 million people worldwide, and ~350,000-500,000 people die every year from HCV-associated hepatic and extra-hepatic complications. HCV has developed numerous mechanisms to evade host immune responses to establish persistence. Due to the lack of a preventive vaccine, the mainstay of current treatment is a combination therapy with interferon-α and ribavirin. The molecular mechanisms underlying the establishment of persistent HCV disease remain poorly understood. A better understanding of these mechanisms would aid design newer therapeutic targets and improve the quality of life of HCV-infected patients Here, we aimed to investigate the role of spontaneous apoptosis of immune cells, expansion of senescent and exhausted virus-specific T-cells, as well as potential depletion of circulating mucosal-associated invariant T (MAIT) cells, with immune impairment in chronic HCV (CHC) disease. We recruited 62 chronically-infected HCV patients and 62 healthy controls (HCs) to conduct a cross-sectional investigation. Peripheral blood mononuclear cells (PBMCs) were isolated, and co-cultured with HCV antigens and phytohaemagglutinin (PHA) individually prior to the investigations (except for apoptosis). Flow cytometry, quantitative real-time PCR (qRT-PCR), ELISA and QuantiGene Plex 2.0 analyses were employed to investigate apoptosis in immune cells. Multiparametric flow cytometry approaches were utilized to examine the phenotypes of immunosenescent T-cells and expression of co-inhibitory molecules on HCV-specific T cells, together with frequencies of circulating MAIT cells. Expression of molecules associated with T-cell inhibition was confirmed by qRT-PCR.